Born–Oppenheimer molecular dynamics simulations on structures of high-density and low-density water: a comparison of the SCAN meta-GGA and PBE GGA functionals. Issue 3 (15th January 2021) - Li, Mengli; Chen, Lu; Gui, Lirong; Cao, Shuo; Liu, Di; Zhao, Gang; Ding, Mingcui; Yan, Jinliang; Wang, Dehua
Abstract : Using Born–Oppenheimer ab initio molecular dynamics (BOAIMD) simulations, the high-density water (HDW) and low-density water (LDW) structures based on SCAN meta-GGA are compared with those based on PBE GGA. Abstract : Using Born–Oppenheimer ab initio molecular dynamics (BOAIMD) simulations, the high-density water (HDW) and low-density water (LDW) structures based on SCAN meta-GGA are compared with those based on PBE GGA. Compared with Car–Parrinello ab initio molecular dynamics (CPAIMD) simulations, BOAIMD simulations can produce more accurate results because no fictitious electron mass is introduced. At each state point, our simulations continue for 100 ps after the system reached equilibrium, which is the longest ab initio simulations of liquid water reported so far and can ensure an accurate statistical average. The influence of the size effect and nuclear quantum effect on structure is not considered in the present work, but only that of two different functionals on the structure is discussed. It is found that, in HDW, just as shown using CPAIMD simulations, the SCAN-based hydrogen-bonds (HBs) are more flexible than the PBE-based ones, which makes the structure based on SCAN obviously closer to the experimental results than that based on PBE. However, it is not the case in LDW, and the difference between the results based on these two functionals is very small.